2019
DOI: 10.4067/s0718-221x2019005000404
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of wood surface coating performance using water based, solvent based and powder coating

Abstract: The objective of this study was to evaluate the surface coating performance using water base, solvent base and powder coating on medium density fiberboard. Samples were coated using water-base, solvent-base and powder coating. Coating performance was performed by using adhesion strength, surface coating hardness, layer thickness and rapid deformation test. The results were analyzed with two different statistical methods. Adhesion strength, layer thickness and surface hardness were determined by using ANOVA ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
1
5
1
Order By: Relevance
“…The distributions of the coatings on and within the veneer were observed using X-ray microtomography. The visibility of the coating, which was successfully visualized using X-ray microtomography, could have been caused by the high number of ions in its chemical composition, which is in accordance with the results of a preliminary study by Ekaputri et al 8 . The coating and woody materials are visible and clearly distinguished.…”
Section: Resultssupporting
confidence: 88%
“…The distributions of the coatings on and within the veneer were observed using X-ray microtomography. The visibility of the coating, which was successfully visualized using X-ray microtomography, could have been caused by the high number of ions in its chemical composition, which is in accordance with the results of a preliminary study by Ekaputri et al 8 . The coating and woody materials are visible and clearly distinguished.…”
Section: Resultssupporting
confidence: 88%
“…This does not diverge from the practical data well known from works [3,9], the authors of which, by the way, also associate a decrease in the quality of wood coating with a change in structural composition. But, unlike the results of studies published in [7,18,19], the obtained data on the effect of thermal modification on the properties of wood, in particular, on degassing, suggest the following:…”
Section: Discussion Of Results Of the Study Of Polymer Shell From Pow...contrasting
confidence: 74%
“…The purpose of study [7] was to evaluate the effectiveness of surface coating using an aqueous base, solvent base, and powder coating on medium-density fiberboard. The coating efficiency was evaluated using adhesion strength, surface hardness, layer thickness -dispersion analysis.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Pull-off adhesion strengths comparable to the adhesion of some commercial organic-based coatings were obtained with CF1, CF7 and CF10-CF12. Adhesion strength values reported in the literature for wood coatings generally range from 2 to 5 MPa, but can reach up to 10 MPa for high performance coatings [23][24][25]. Based on observations of six polyurethane coatings, Oblak and co-authors [26] suggested a minimum acceptable adhesion value of 2.5 MPa for wood, and more than 5 MPa for excellent adhesion.…”
Section: Coating Performancesmentioning
confidence: 99%